2016
DOI: 10.1155/2016/5781579
|View full text |Cite
|
Sign up to set email alerts
|

TheGinkgo bilobaExtract Reverses the Renal Effects of Titanium Dioxide Nanoparticles in Adult Male Rats

Abstract: The Ginkgo biloba extract (GbE) is a commercial product used as a nutraceutic herbal remedy in Europe and US. It contains 27% of the polyphenols isorhamnetin, kaempferol, and quercetin, as antioxidants. We used male adult Wistar rats (200–300 g), divided into four groups: control group (treated with 5.0 mg/kg of sodium chloride, intravenous), titanium dioxide nanoparticles (TiO2-NPs) group (5.0 mg/kg, intravenous), GbE group (10 mg/kg, intraperitoneal), and GbE + TiO2-NPs group (treated 24 h before with 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Ginkgo biloba (GB) leaf extract has widely consumed as herbal nutritional and used in the treatment and prevention of a variety of diseases as cognitive enhancers [12]. Gingko contains high levels of flavonoids and terpenoids, antioxidants that provide protection against oxidative cell damage from harmful free radicals [13][14][15]. L-carnitine is a naturally occurring amino acid derivative that's often taken as a supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgo biloba (GB) leaf extract has widely consumed as herbal nutritional and used in the treatment and prevention of a variety of diseases as cognitive enhancers [12]. Gingko contains high levels of flavonoids and terpenoids, antioxidants that provide protection against oxidative cell damage from harmful free radicals [13][14][15]. L-carnitine is a naturally occurring amino acid derivative that's often taken as a supplement.…”
Section: Introductionmentioning
confidence: 99%
“…These results go on hand with previous data [ 30 , 44 ], whereas the concomitant treatment with BB extract showed noteworthy improvement of the major analyzed parameters. In fact, BB is a good source of polyphenols and flavonoids, antioxidants known to be effective against toxicity and renal damage induced by titanium nanomaterials; recently, it was suggested that polyphenols and flavonoids exert their nephroprotective effects following their interaction with the cytoplasmic membrane of renal tubule cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%